Alokasi Pendapatan Rumah Tangga Nelayan - Vadli, Vadli; Abdullah, Sukmawati; Limi, Muhammad Aswar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
The purpose of this study was to analyze the allocation of fishermen's household income in South Konawe Regency. This research will be conducted in the area of Kolono Timur Subdistrict, South Konawe Regency. The population in the study were fisherman households in Kolono Timur Subdistrict, totaling 104 households, which had income sources originating from fishermen. To guarantee the representation of the population in each household, 15% of the total source of income was taken as a sample in the study (Rianse and Abdi, 2009). The sampling technique is simple random sampling, with determination criteria that actually represent the sample. The criteria referred to are households originating from livelihoods from fishermen. The samples obtained in this study were 31 families. Research variables include the allocation of household income consisting of food and non-food needs in one month's time frame. Analysis Data on the allocation of fishermen's household income is done by recording the average monthly usage. Based on the results of the analysis, it can be found that the average budget allocation of income is Rp.714,264- / month or 40.20% for food needs and Rp.1,062,742- / month or 59.80% for non-food needs. While the average difference between total income and the average household income allocation for fishermen respondents is Rp.2,851.714- / month. The allocation of household income will reflect the income earned so that it is necessary to conduct similar studies to examine the problems that exist in households based on household income allocation.